Targeted and Biomimetic Nanoparticles for Atherosclerosis Therapy: A Review of Emerging Strategies - Dorota Bartusik-Aebisher; Rafał Podgórski; Iga Serafin; David Aebisher (Biomedicines)
Atherosclerosis, a chronic inflammatory disease, remains a leading cause of cardiovascular mortality worldwide. Despite standard treatments like statins and percutaneous coronary intervention (PCI), significant residual risk and therapeutic limitations underscore the need for innovative strategies. This review summarizes recent advances in nanoparticle-based therapies for atherosclerosis, focusing on key developments from the last five years. We discuss various nanoplatforms designed to selectively target key cellular players in plaque pathogenesis, including macrophages, endothelial cells, and vascular smooth muscle cells (VSMCs), to inhibit inflammation, modulate cellular phenotypes, and stabilize plaques. A significant focus is placed on the emerging field of biomimetic nanoparticles, where therapeutic cores are camouflaged with cell membranes derived from macrophages, platelets, neutrophils, or erythrocytes. This approach leverages the natural biological functions of the source cells to achieve enhanced immune evasion, prolonged circulation, and precise targeting of atherosclerotic lesions. Furthermore, the review covers nanoparticles engineered for specific functional interventions, such as lowering LDL levels and exerting direct anti-inflammatory and anti-oxidative effects. Finally, we address the critical challenges hindering clinical translation, including nanotoxicity, biodistribution, and manufacturing scalability. In conclusion, nanotechnology offers a versatile and powerful platform for atherosclerosis therapy, with targeted and biomimetic strategies holding immense promise to revolutionize future cardiovascular medicine.